IMPLEMENTASI MEDIA PEMBELAJARAN INTERAKTIF DENGAN PERMAINAN LOKAL DALAM PENGUATAN KARAKTER PADA MATA PELAJARAN PPKn - Yasmin, Regita; Rejeki, Sri; Winata, Aliahardi (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This study aims to determine the impact of local games (X) on students' character development (Y). A quantitative research method was employed, collecting data via questionnaires with 15 items for the local games variable (X) and 15 for the character assessment variable (Y). The research procedure included instrument preparation, instructional process, data analysis, interpretation, and conclusion formulation. The findings indicate that local games influence students' character development, with an average score of 85.69. The F-statistic value of 0.06 and significance level of 0.941 suggests that while local games impact character development, not all character aspects are significantly affected. The character trait of